2014
DOI: 10.1194/jlr.m041863
|View full text |Cite
|
Sign up to set email alerts
|

CD36-deficient mice are resistant to alcohol- and high-carbohydrate-induced hepatic steatosis

Abstract: liver failure ( 2 ). As a fi rst stage in the ALD spectrum, alcoholic steatosis has been extensively studied in humans and animal models to better understand the mechanisms leading to fat accumulation in the alcohol-exposed liver. This research has indicated that alcohol has many effects on hepatic lipid metabolism, including dysregulation of pathways associated with fatty acid (FA) synthesis, uptake, and oxidation, and triglyceride (TG) synthesis and export; however, the mechanisms underpinning these changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 42 publications
6
54
1
1
Order By: Relevance
“…Although CD36/FAT does not play a major role in fatty acid uptake in normal liver [40,41], increased hepatic CD36/FAT expression has been observed in various pathologic conditions such as cancer, NAFLD, and type 2 diabetes mellitus [42,43]. Similarly, CD36/FAT levels were up-regulated in CerS2 null mice, although CD36/FAT was non-functional since it was mis-localized, likely due to altered membrane properties [12,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although CD36/FAT does not play a major role in fatty acid uptake in normal liver [40,41], increased hepatic CD36/FAT expression has been observed in various pathologic conditions such as cancer, NAFLD, and type 2 diabetes mellitus [42,43]. Similarly, CD36/FAT levels were up-regulated in CerS2 null mice, although CD36/FAT was non-functional since it was mis-localized, likely due to altered membrane properties [12,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CD36, the fatty acid translocase, is upregulated in mice lacking ACE2 (Figure 3). It has been shown that the upregulation of CD36 in the liver is associated with increased steatosis in NAFLD patients [29, 30] and CD36 −/− mice are resistant to alcohol and high carbohydrate-induced hepatic steatosis [31]. Moreover, in mice and humans aging increases CD36 membrane expression in the liver [29], causing increased fat uptake and advancing NAFLD with age.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol also modulates the expression of lipoprotein receptors in the liver to regulate uptake of fatty acids released from the adipose tissue. Accordingly, chronic alcohol intake increased CD36 [7,57,58,59] and very low density lipoprotein receptor (VLDLR) expression in the liver [60], whereas knock-out of these receptors protected mice from the development of alcohol-induced fatty liver [57,60]. In contrast, chronic alcohol intake decreased VLDLR and LPL [60] and did not change CD36 expression in WAT [7], indicating differential regulation between tissues and potentiation of the lipolytic phenotype induced by alcohol.…”
Section: Regulation Of Lipid Balancementioning
confidence: 99%
“…In contrast, the effects of alcohol on the expression of FATPs in the liver are inconsistent and differ with each form. FATP1 has been reported to be increased [61], decreased [58], and unchanged [57,59]; similarly, changes in FATP2 and FATP5 are also variable within and across studies in chronic alcohol-fed animals [7,57,58,59,61]. …”
Section: Regulation Of Lipid Balancementioning
confidence: 99%